Petrology and geochemistry of peridotites and podiform chromitite in the Xigaze ophiolite, Tibet: Implications for a suprasubduction zone origin. (15th September 2017) - Xiong, Fahui; Yang, Jingsui; Robinson, Paul T.; Gao, Jian; Chen, Yanhong; Lai, Shengming
Graphical abstract: Highlights: High-Cr chromitites were firstly found in the Xigaze ophiolite. High-Cr chromitites derived from a boninitic melt, indicate the formation of Xigaze ophiolites is a multi-stage process. Rare earth elements and platinum group elements of peridotite indicate refertilization of depleted peridotites by suprasubduction melts. Abstract: The Xigaze ophiolite, which lies in the middle section of the Yarlung Zangbo suture zone (YZSZ) of southern Tibet, is composed from the base upward of tectonized harzburgites with minor dunites, and a magmatic sequence of wehrlites, pyroxenites, troctolites and gabbros. Both abundant high-Cr, metallurgical and sparse, dunites occur within the harzburgites. The peridotites show abundant evidence of mantle melt extraction at various scales as indicated by the Fo values of olivine (92.4–93.5) in the harzburgites and 92.8–94.0 in the dunites. Whole-rock MgO contents are 41–50 wt%, similar in composition to forearc peridotites. Most of the chromitites have high Cr# numbers (61–81), although there are systematic changes in olivine and chromian spinel compositions from harzburgites, to dunites to chromitites, reflecting variable partial melting and melt-rock reaction. The primitive mantle U-shaped rare earth element (REE) patterns of the harzburgites indicate refertilization of depleted peridotites by suprasubduction melts. The PGE abundances in the Xigaze rocks provide additional constraints on their geochemical evolution and show multiple episodes of melt extraction from the mantle source, giving it a subchondritic character. Compositional zoning of minerals likewise attest to modification by migrating melts, formed in a suprasubduction zone mantle wedge.